2018
DOI: 10.1051/e3sconf/20183303065
|View full text |Cite
|
Sign up to set email alerts
|

Socioecological Aspects of High-rise Construction

Abstract: In this article, the authors consider the socioecological problems that arise in the construction and operation of high-rise buildings. They study different points of view on high-rise construction and note that the approaches to this problem are very different. They also analyse projects of modern architects and which attempts are made to overcome negative impacts on nature and mankind. The article contains materials of sociological research, confirming the ambivalent attitude of urban population to high-rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Perera et al [9], for instance, reported that many high-rise luxury projects have been erected in Sri Lanka during the last decades, and many of them will be completed in the not-too-distant future. A similar trend has been witnessed in other countries such as Hong Kong [10], Russia [6], and the UK [11]. The rapid growth of the population is certainly a reasonable explanation for this trend.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…Perera et al [9], for instance, reported that many high-rise luxury projects have been erected in Sri Lanka during the last decades, and many of them will be completed in the not-too-distant future. A similar trend has been witnessed in other countries such as Hong Kong [10], Russia [6], and the UK [11]. The rapid growth of the population is certainly a reasonable explanation for this trend.…”
Section: Introductionsupporting
confidence: 77%
“…Some definitions and codes merely considered height as the main aspect. Farouk [5], for example, considered a high-rise building as one whose total height exceeds Buildings 2021, 11, 504 2 of 18 36 m. Based on Russian building codes, buildings rising between 75 and 150 m are classified as high-rise buildings [6]. On the contrary, some others paid more attention to the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this we add, in this research, the classical sociological contributions alluded to above, so that we will observe the verticalization of North American cities as a sacred symbol, germ of aesthetic, economic, and technical reasons (Eichner and Ivanova, 2017: 1). Thus, skyscrapers will be understood as a comprehensive form, as a sociological object, as a syntagm – Lefebvre – that relates them to the sociocultural–religious–economic context – Beltrán – to the urban space, to the institutional logics turned into ‘guiding principles of society’ that ‘guide social action’ (Greenwood et al, 2010: 521).…”
Section: Introductionmentioning
confidence: 99%
“…It is a challenging task for architects to design common areas in RHBs for different people and cultures, as the design should integrate the needs of different groups of people to achieve social sustainability. Experts believe that RHB design plays a vital role in the cultural life of different communities, which should be properly considered, provided and maintained (Eichner et al, 2018) The main objective of this research is to provide an overview of various sustainability factors, such as environmental, economic and social aspects, in relation to RHB buildings. This paper provides information concerning the sustainability strategy in general, and the effects of this type of buildings on the surrounding environment in relation to the three factors mentioned above.…”
Section: Introductionmentioning
confidence: 99%